Contemporary funeral rituals of Sa'dan Toraja : from Aluk Todolo to new religions - Budiman, Michaela (Karolinum, 2013)
Contemporary Funeral Rituals takes you inside the fascinating world of the Sa'dan Toraja, who inhabit the Indonesian island of Sulawesi. The author explores first-hand the most important contemporary Toraja ritual - the funeral - and documents and analyses the changes brought about by the Toraja leaving their autochthonous religion Aluk Todolo behind and embracing Christianity during the last century.